The cytological component of cervical cancer screening: causes of false negative and false positive results, and ways to avoid them - O.A. Burka; N.F. Lygyrda; V.V. Kutsovol; A.V. Svintsitska (Publishing House TRILIST, 2021)
Cervical cancer (CC) screening is a major component of secondary prevention of CC and involves screening all women at risk of developing this disease, most of whom are asymptomatic. Cytology remains an important component of CC screening in the era of primary screening by genotyping the human papillomavirus. Papanikolaou staining is the method of choice for CC screening. This review highlights the causes of false negative results for various methods of Pap tests and how they can be prevented. A detailed analysis of conditions accompanied by a high probability of false positive abnormal results of the Pap test, an explanation of the pathophysiological basis of this phenomenon, clinical and cytological criteria for differential diagnosis is also presented. Pap test is a screening test. The aim of the cytological examination in CC screening is to assign the patient to a group with absent neoplastic changes in the cervical epithelium, a group with neoplastic changes in the cervical epithelium present, or a group when it is impossible to make an accurate differential diagnosis between benign reactive changes and neoplasia. The Bethesda Cytology Reporting System is used to unify and standardize these categories in most countries of the world. Benign conditions are a common cause of false positive reports of cellular atypia on cervical screening, as evidenced by a large number of studies. This fact should be taken into account both in the interpretation of the results and, if possible, in the planning of cervical screening. The most common conditions that are accompanied by reactive changes in the cervical epithelium, which can be incorrectly assessed as atypia, are: reactive and reparative inflammatory changes, atrophy, metaplasia, reactive changes caused by intrauterine devices. In this regard, when working with the cytological component of cervical screening, it is important for the clinician to understand the basic principles of assessing the cervical epithelium, which will allow using the descriptive part of the report to determine tactics if a false negative or false positive screening result is suspected. Thus, understanding the impact of common benign conditions on the cervical epithelium makes it possible to rationally plan cytological cervical screening and correctly interpret its results in order to achieve the best clinical results that are not limited to the detection of precancerous conditions.